Mecanismos de controle da mancha bacteriana do tomateiro exercidos por rizobactérias - Mates, Aveline de Paula Kuyat (2017)
Tomato cultivation and processing is concentrated in the Southeast, Midwest and Northeast brazilian states. Among diseases that affect the culture, the bacterial spot is one of the most important. The bacterial spot is caused by four different species of bacteria belonging to Xanthomonas. Its control is difficult, with perspectives of the use of antagonistic microorganisms, since conventional control measurements do not present satisfactory efficiency. The use of bacteria of the genus Bacillus spp. is one of the viable alternatives in the control of diseases and in the reduction or substitution of the use of agrochemical products in the control of plant diseases. Therefore, the objective of this research was to define by the capability and the mechanisms that previously selected isolates of Thiobacillus sp. and Bacillus spp. promote the control of the bacterial spot of the tomato. Seven previously selected isolates of Bacillus spp. and one isolate Thiobacillus sp. (GF193, GF264, GF267, GF267, GF271, GF434, GF435, and GF451) were tested with single carbon sources to verify niche overlap, antibiosis, siderophore production, capability to control the bacterial spot, enhancement of the chlorophyll content, and resistance induction. On in vitro assays, the isolates GF203, GF264, GF267 and GF451 inhibited the development of X. perforans. Isolates GF193, GF203, GF264, GF267, GF271, GF435 and GF451 were able to produce siderophores. The GF267 isolate was able to compete for carbon sources against X. perforans. On in vivo assays, the GF267 isolate was the most efficient in reducing the severity of bacterial blight both dispensed on leaves and plant roots. The peroxidase and polyphenoloxidase activities of were increased at 3 and 5 days after inoculation of the pathogen on plants with application of GF267, evidencing this strain is able to induce systemic resistance in tomato. The antagonist was also able to increase the chlorophyll content on plants in the initial disease development period by root colonization. It was concluded that GF267 (B. methylotrophicus) was the most promising strain on the control of the bacterial spot of the tomato by direct antagonism and resistance induction.